Teaching and Learning in a First-Year Writing Skills Transfer Course: Investigating College Professor and Student Experiences - Tremblay, Taunya; Zeppa, Jamie; Blake, Shannon; Bolton, Kiley; Ohlsson, Katarina; Dalton, Christine; Yeoman, Victoria; John, Lavaughn (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
When Seneca Polytechnic replaced EAC150, an essay-based English course, with COM101, a first-semester writing course based on writing skills transfer, we saw the opportunity to investigate both professors’ and students’ experiences of the new approach. Specifically, we wanted to know how professors conceptualized and taught COM101 and also how students connected their writing for COM101 with other writing they did at Seneca, their workplaces, and in their personal lives. From 2018–2020 we conducted qualitative surveys with professors and mixed-method surveys with students and applied inductive, thematic coding to all qualitative data. The data results were encouraging: student responses indicated that COM101 positively affected their writing and reported transferring writing skills to other areas of their lives. In addition, professor responses indicated that they actively engaged with skills transfer pedagogy, despite the fact that COM101 demanded a significant change in approach. In professor responses that indicated resistance to the new approach we found valuable lessons about the core ideas of transfer, including negative transfer, and the difficulties that anyone – professors and students alike – face in new learning situations.